Pemberdayaan Pelaku UKM Pada Dinas Koperasi, UKM Dan Perdagangan (KOPUMDAG) Kabupaten Maros - Suhermanto, Suhermanto; Fatmawati, Fatmawati; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2021)
This study purposed to find out the empowerment of small and medium businesses (UKM) in the Office of UKM cooperatives and trade in Maros Regency. This study used descriptive qualitative method that gave picture or explanation objectively related to the actual state of the object under study. Data collection techniques were interviews and observation and documentation. The results of this study showed that empowerment (UKM) at the Office of Kopumdag was not running optimally. Empowerment carried out by the government in the initial phase was quite instrumental by providing training and counseling. Furthermore, in the participatory phase the community and government had collaborated in developing UKM. While in the emancipatory phase the government was still constrained by the provision of facilities and infrastructure in developing UKM. Therefore, the empowerment of UKM in Maros Regency should provide adequate facilities and infrastructure, so that the implementation of training or counseling could run optimally and produced output that was in line with expectations.